2014
DOI: 10.1139/tcsme-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Design, Simulation and Bifurcation Analysis of a Novel Micromachined Tunable Capacitor With Extended Tunability

Abstract: In this paper, a novel RF MEMS variable capacitor has been presented. The applied techniques for increasing the tunability of the capacitor are the increasing of the maximum capacitance and decreasing of the minimum capacitance. The proposed structure is a simple cantilever Euler–Bernoulli micro-beam suspended between two conductive plates, in which the lower plate is considered as stationary reference electrode. In this structure, two pedestals are located in both tips of the cantilever beam. In the capacitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Due to the nonlinear nature of the electrostatic force applied between the two capacitive electrodes as well as the pull-in instability present in the system, the relative displacement between the electrodes cannot exceed a certain distance. Considerable relative displacements between capacitive electrodes, for example in tunable micro capacitors, is of great importance [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the nonlinear nature of the electrostatic force applied between the two capacitive electrodes as well as the pull-in instability present in the system, the relative displacement between the electrodes cannot exceed a certain distance. Considerable relative displacements between capacitive electrodes, for example in tunable micro capacitors, is of great importance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this end, some modification implemented in the design and fabrication process of the micro capacitors [2,13,14]. These changes complicated the design and construction process, as well as increased costs.…”
Section: Introductionmentioning
confidence: 99%
“…Azizi et al [37] studied bifurcation Behavior of a Capacitive three layer microswitch. Mobki et al [38] designed and analyzed a new micromachined tunable three layer capacitor with extended tenability. Azimloo et al [39] Shah-Mohammadi-Azar [40] presented Angular Velocity Sensors based three layer switch and studied their pull-in behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Actuated MEMS/NEMS devices are widely utilized in inkjet printers, switches, gyroscopes, chemo-sensors, micro-manipulators and so on. Recently, several numerical and experimental studies have been conducted on the pull-in instability, static and dynamic behavior of MEMS/NEMS devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Vibrations of electrostatically actuated microbeams have been analyzed by Batra et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…Batra et al [11] considered the von Kármán nonlinearity and the Casimir force and developed a reduced-order model for a pre-stressed elliptic electrostatically actuated microplate and studied the vibrations and pull-in instability of micro-structures. A new structure to increase the tunability of RF variable MEM capacitor was presented by Mobki et al [12]. They showed that by decreasing the minimum capacitance and increasing the maxi-mum capacitance, more tunability could be achieved.…”
Section: Introductionmentioning
confidence: 99%